A doctorate and beyond : building a career in engineering and the physical sciences - Goodwin, Graham C. 1945-; Graebe, Stefan F. (Springer, 2017)
A book that takes you through and beyond your doctoral studies. It will be a valuable reference throughout your working life. Drawing on their own extensive experience, the authors pass on invaluable advice by answering such questions as: Do I want to do a doctorate? How should I choose which doctorate and where to study? How do I achieve my doctorate? What career opportunities exist once I've completed my doctorate? What is the role of networking, leadership and reputation in building my career? How do I go about mentoring the next generation? What do I do when things don't go to plan? This practical guide helps you to determine your best answer to all these questions and more. The authors not only discuss how to become a success but also how to keep success going, beginning with the choice to do a doctorate (or not) and what to expect, through how to get the best from student-supervisor interaction, the value of networking, the process of publication, how to choose between a career in academia or industry, while achieving work-life balance. The authors' own thoughts are enriched by the life experiences of many colleagues and prominent individuals who have achieved success and recognition: the book contains inspirational quotes from established figures in academia and industry. They reflect on career options, what leads to a successful career, and how to make conscious career choices instead of letting things happen and hoping for the best. This ranges from avoiding common pitfalls-such as squandering your reputation-to developing that all-important energy: your personal passion. A Doctorate and Beyond will be an extra difference in making the most of the best times and will support you when the going gets tough. If you are contemplating doctoral studies in engineering or the physical sciences, or have a doctorate and are seeking career guidance, this book will change the way you think about life.
Keywords: Engineering -- Vocational guidance.; Engineering -- Study and teaching (Graduate); Science -- Study and teaching (Graduate); Science -- Vocational guidance.; Doctoral students.; elektronické knihy; electronic books